A Review of the Translation of Field Methods in Archaeology - Kourosh Roustaei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper critically reviews the Farsi translation of the book entitled Field Methods in Archaeology. The aim of this paper is to evaluate and discuss the quality of the Farsi translation by presenting some of the shortcomings and misunderstanding frequently occurring in the translated book. These shortcomings are classified, exemplified, and discussed by numerous sentences, phrases, and technical and ordinary terms and words as well. The main arguments are discussed under the following subjects: imprecise translation, vague or wrong translation, difficult reading, and inconsistencies in translation. Perhaps, the most obvious problem of the reviewed book is verbatim or literal translation. Lacking rightful and clear understanding of the original text is another major pitfall of the translated book. Using wrong, improper, or vague equivalents is still a further problem of the book under review. These subjects have been exemplified by many examples